Knowledge of newborns’ mothers on breastfeeding during covid-19, hiv and tuberculosis infection attendee in selected hospitals (Journal of Preventive and Social Medicine, 2024)
Background: Two-thirds of the HIV mothers planned to breastfeed their infants while one-third opted for formula feeding; same as during Tuberculosis or COVID-19 infection. What would be the mother do during breastfeeding? Whether the mother could breastfeed their newborn or not. For that it is necessary to assess the level of knowledge of newborns mother on breastfeeding during COVID-19, HIV and Tuberculosis. Methods: It was a descriptive type of cross sectional study was conducted at Maternal and Child Health Training Institute, Azimpur, Dhaka from 1st January to 31st December 2021. Mother of newborns who are willing to participate were conveniently selected. Around 289 sample was selected. Pre tested semi structured questionnaire was used to collect the data. Level of knowledge was measured by knowledge score. Each question of knowledge carries one (01) mark. Each correct answer had 1 mark and incorrect answer had 0 mark. 1-11 score (